2022
DOI: 10.3390/curroncol29070383
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Evidence for Exercise Oncology within Breast Cancer Care

Abstract: Exercise is safe and effective for those living with and beyond breast cancer, with evidence supporting exercise guidelines, and position statements from international organizations. Despite the clearly recognized benefits of exercise for these individuals, many do not participate or maintain recommended exercise levels throughout the breast cancer continuum, highlighting the lack of translation from research into practice. In addition, discerning how exercise can be tailored to address breast cancer-related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Despite these limitations, the current qualitative findings, in conjunction with the quantitative findings [ 23 ] support the role of a multiphasic exercise prehabilitation program across HNC clinical care. To support implementation, screening, triage, and referral pathways across the HNC continuum may support earlier access to evidence-based exercise resources for patients, as well as support better adherence to exercise programming [ 19 , 42 , 43 , 44 ]. In addition, supporting exercise adherence needs to extend beyond the individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, the current qualitative findings, in conjunction with the quantitative findings [ 23 ] support the role of a multiphasic exercise prehabilitation program across HNC clinical care. To support implementation, screening, triage, and referral pathways across the HNC continuum may support earlier access to evidence-based exercise resources for patients, as well as support better adherence to exercise programming [ 19 , 42 , 43 , 44 ]. In addition, supporting exercise adherence needs to extend beyond the individual.…”
Section: Discussionmentioning
confidence: 99%
“…The Social Ecological Model [ 45 ] posits that behavior change is indeed influenced by interactions between these multiple environments. Thus, exercise oncology interventions must target multiple levels to support exercise adherence, considering interactions between patients, their healthcare providers, and the exercise specialist team, in order to build a pathway that supports a multiphasic exercise prehabilitation approach, ultimately building resources to support exercise into cancer survivorship that are sustainable in community-based settings [ 19 , 42 ]. To that end, tailoring interventions that focus on tumor type, treatment type, place on cancer continuum, side-effects from treatment, and individual factors is also important to enhance recruitment and adherence to exercise programming [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that self-induced movement has key effects in the synthesis and release of hormones and peptides strongly involved in brain modulation [94][95][96] . Exercise has been suggested as the must for improvement of quality of life after breast cancer [97][98][99][100] . However, patients are constantly dealing with fatigue, sleeping disorders and pain, which may prevent them from regular voluntary exercise routines.…”
Section: Discussionmentioning
confidence: 99%
“…Since targeted outreach began, there have been 22 participants in two successful, lung-specific exercise classes in 2022. This targeted outreach and delivery of classes will be expanded to reach other underserved tumour types, including for individuals with an advanced cancer diagnosis that require specific exercise tailoring to meet functional and movement needs [25,26].…”
Section: Reach and Adoptionmentioning
confidence: 99%
“…This is not surprising, given commonly reported HCP barriers to exercise-oncology referral, including a lack of time, knowledge, and resources about exercise and cancer [33], as well as limitations to in-person interactions associated with the COVID-19 pandemic (i.e., less facetime between HCPs and patients in clinical settings). Although enrolment through self-referral highlighted the effective community-based outreach from the EX-CEL hubs, the HCP referral pathway is critical for sustainability within the cancer care system [14,25]. Ongoing work in both neuro-oncology [34] and head and neck cancer [35] populations are utilizing rehabilitation triage clinics in collaboration with physiatrists within cancer care settings to embed both exercise screening and referral into clinical workflows.…”
Section: Reach and Adoptionmentioning
confidence: 99%